2008
DOI: 10.1007/s11270-008-9687-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composting on Polycyclic Aromatic Hydrocarbons Removal in Sewage Sludge

Abstract: Changes in the concentrations of 16 polycyclic aromatic hydrocarbons (PAHs) identified by the US Environmental Protection Agency as priority pollutants were investigated during the composting process of sewage sludge mixed with rapeseed marc (9:1, weight base). Results showed that total PAHs concentrations of the sludge sampled in different seasons had far exceeded the accepted Europe Union cut-off limits for land application. Phenanthrene, fluorene and dibenz(a, h) anthracene were dominant PAHs in the sludge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Hua et al (2008) detected that total PAH concentrations in sludge in different seasons far exceeded the proposed European Union limits for sludge applied to soil. Feng et al (2014) found that the PAH content of sludge-amended soil increased as the sludge dose increased and that some PAHs were taken up from the soil by plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al (2008) detected that total PAH concentrations in sludge in different seasons far exceeded the proposed European Union limits for sludge applied to soil. Feng et al (2014) found that the PAH content of sludge-amended soil increased as the sludge dose increased and that some PAHs were taken up from the soil by plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al (2008) observed a maximum temperature of 65°C on day 7 while composting polycyclic aromatic hydrocarbons in sewage sludge which then declined to 35°C after 15 day and reached ambient temperature after 30 days. Ghaly et al (2007) reported maximum steady temperatures of 32 and 40°C after 60 h for continuous and intermittent mixing during the bioremediation of toluene contaminated soil.…”
Section: Discussionmentioning
confidence: 97%
“…According to Walker et al (1999), an intense decrease of moisture content will reduce the metabolic rate and affects the effectiveness of the bioremediation process while high moisture content can reduce the oxygen transfer. Hua et al (2008) reported a steadily decreasing trend of moisture content from an initial value of 62.5% to a final value of 30.2% after 60 days during the composting of sewage sludge mixed with rapeseed marc. Guardia et al (2010) observed a decrease in the moisture content of composted food waste with wood chips the mixture from 63.4-50.5% after 37 days of composting.…”
Section: Moisture Contentmentioning
confidence: 97%
“…In fact, the handling of biosolids and the achievement of environmentally sound and economically feasible disposal strategies are currently major issues in wastewater treatment, not only in Swaziland but in many places around the world (Deepesh et al 2014;Fytili and Zabanitou 2008;Contin et al 2012). The controlled application of biosolids in mine sites can greatly improve soil physicochemical conditions since these organic residues contain organic matter (OM) that acts as a soil conditioner which can improve soil aeration, waterholding capacity (Bourioug et al 2014;Hua et al 2008;Wong et al 1998, etc. ), contributing to erosion control, slope stabilization (Luczkiewicz 2006) and aggregate stability (Bozkurt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, since land application of biosolids is still generally regarded as controversial due to possible human health and environmental risks (Luczkiewicz 2006), on account of elevated metal concentrations contained therein (Bourioug et al 2014;Hua et al 2008;Forsberg and Ledin 2006;etc. ), the SWSC commissioned a number of studies to investigate the impacts of biosolids in mine soils with regard to various aspects including soil physicochemical conditions, plant establishment and growth and metal accumulation in plants.…”
Section: Introductionmentioning
confidence: 99%